Digital Preparation of Companies in the Pandemic Period: An Analysis of the Financial Services Sector of Maringá-PR (Management and Connections Journal, 2023)
The advent of the covid-19 pandemic required changes in the way individuals interact with each other, in labor relations, and also in the consumption of goods and services, which have become much more digital. Thus, in this qualitative study we sought to analyze the digital preparation of companies in the financial services sector of Maringá-PR, from the impacts of the pandemic, according to the criteria of Marketing 5.0. 15 companies were interviewed, through a semi-structured script of questions. Then, the data were analyzed and the companies were framed in their respective digital preparation profiles. It was found that the companies grew in the pandemic period and used the learnings of this time to structure digital processes. However, your customers still have trust problems in entirely digital interactions, and therefore prefer to have the first physical contact before migrating to virtual interactions.
Keywords: digital preparation; financial services; digital marketing; marketing 5.0; covid-19 pandemic